The use of gender-sensitive language and the representation of women in print media in Serbia - Begović, Bojana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
The struggle for gender equality can be seen through the attitude towards women and women representation in the media, as public opinion makers. The aim is to analyze the use of gender sensitive language and the representation of women in politics sections of the Serbian print media Blic, Kurir and Danas. The research is using quantitative and qualitative analysis of discourse. The selected material was analyzed using a unique coding system that is tailored for print media. Sample for the analysis consists of media announcements of the selected media in the period from 1 to 7 June 2015. The research results point to the conclusion that the use of gender-sensitive language in the considered media is on a relatively satisfactory level and that print media in Serbia, when it comes to texts on politics, mostly do not contain discrimination against women. However, men are predominantly represented in the media, particularly in the political sphere. Women are mentioned rarely, and when they are, they are not protagonists of a story. This suggests that we must continue to work on educating citizens, particularly those in public offices.
Keywords: gender sensitive language; gender equality; media representations; politics; print media